2001
DOI: 10.1038/sj.onc.1204057
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the Smad4 gene in acute myelogeneous leukemia and their functional implications in leukemogenesis

Abstract: The Smad family proteins are critical components of the transforming growth factor (TGF)-b signaling pathway. TGF-b is a multipotent cytokine that elicits many biological functions. In particular, TGF-b exhibits e ects on the cell cycle manifested by G1-phase arrest, di erentiation, or apoptosis of several target cells, suggesting that disruption of TGF-b signaling pathway could be involved in cancer formation. Here we show one missense mutation of the Smad4 gene in the MH1 domain (P102L) and one frame shift m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(189 citation statements)
references
References 36 publications
9
179
1
Order By: Relevance
“…132 Some monoallelic mutations may act in a dominant-negative manner through inhibition of the effects the remaining WT AML1. This hypothesis was confirmed by Osato et al and Imai et al, 124,126 who demonstrated that some AML1 gene missense mutation cotransfected with WT AML1 abolished transactivation of the M-CSF receptor promoter. Moreover, Imai et al 126 demonstrated that this dominant-negative effect was due to the fact that the mutated protein did not bind DNA but had enhanced capacity to bind CBFb and, by sequestering it, inhibited action of WT AML1, as observed for chimeric products of t(3;21) or t(8;21) translocations.…”
Section: Aml1supporting
confidence: 75%
See 1 more Smart Citation
“…132 Some monoallelic mutations may act in a dominant-negative manner through inhibition of the effects the remaining WT AML1. This hypothesis was confirmed by Osato et al and Imai et al, 124,126 who demonstrated that some AML1 gene missense mutation cotransfected with WT AML1 abolished transactivation of the M-CSF receptor promoter. Moreover, Imai et al 126 demonstrated that this dominant-negative effect was due to the fact that the mutated protein did not bind DNA but had enhanced capacity to bind CBFb and, by sequestering it, inhibited action of WT AML1, as observed for chimeric products of t(3;21) or t(8;21) translocations.…”
Section: Aml1supporting
confidence: 75%
“…122,123 Other mechanisms of AML1 inactivation have been reported in hematological malignancies, through point mutations, in AML and in MDS. [124][125][126][127][128][129] Both germ-line and acquired AML1 mutations have been reported in hematological malignancies. Germ-line mutations of the AML1 gene have initially been reported by Song et al in very rare cases of familial platelet disorder with predisposition to AML (FPD/AML).…”
Section: Aml1mentioning
confidence: 99%
“…He remains in continuous remission with maintenance chemotherapy 10 months after diagnosis. The karyotype was: 46,XY,add(1)(q25),add(21)(q21) [6]/46, XY [14]. FISH analysis did not reveal ETV6/AML1 fusion, but an AML1 gene amplification with eight copies on interphase cells.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA-binding ability is severely impaired in R139G, although the ability to heterodimerize with CBF␤/PEBP2␤ is spared. 21 This mutant could not restore hematopoiesis. These results suggest that, in the presence of an intact Runt domain, the transcriptional activating function is necessary and sufficient for Runx1 to rescue the hematopoietic defect of Notch1-null mice in the P-Sp culture system, while the transcriptional repressing function is dispensable.…”
Section: Functional Implication Of Runx1 At the Downstream Of Notch-rmentioning
confidence: 96%